PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK PENGELOLAAN LIMBAH RUMAH TANGGA DI KAWASAN PESISIR DESA KADACUA, KECAMATAN KULISUSU, KABUPATEN BUTON UTARA - Said Sales Salihi; Deki Pradana (JICS : Journal Of International Community Service, 2025)
This community service program focuses on implementing appropriate technology to address household waste problems in coasal areas. Through a participatory approach that actively involves the community The applied technologies include biopore infiltration holes for water absorption and composting, household-scale composters, and simple wastewater treatment systems designed according to local conditions. Program evaluation results show a significant increase in the commu nity's capacity to manage organic waste into economically valuable compost, accompanied by a 65% reduction in inorganic waste volum e through sorting and recycling programs. The formation of an independent waste management group consisting of local residents serves as an indicator of the program's success in creating long-term sustai nability mechanisms. This program has not only successfully raised environmental awareness in the community but has also tangibly rea lized healthier, cleaner, & more sustainable coastal areas for future generations through behavioral & establishment of local institutions.